Implementasi Manajemen Peserta Didik Dalam Peningkatan Mutu Madrasah Di MTs Raden Rahmat Selorejo Mojowarno - Solechan Solechan; Aris Setiawan (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2021)
Student management includes the entire process of managing students in an education system that includes needs analysis until students become alumni. This study aims, first, to describe the implementation of student management at MTs Raden Rahmat Selorejo Jombang. Second, describe the quality of madrasas at MTs Raden Rahmat Selorejo Jombang. This research uses a qualitative approach with the type of case study research. Data collection methods include observation, interviews and documentation. The data analysis technique uses the Miles and Huberman interactive model which includes data reduction, data presentation and conclusion drawing. The results obtained first, the implementation of students at MTs Raden Rahmat Mojowarno includes recruitment: selection of prospective students, dissemination of information, registration requirements, and implementation of recruitment. Second, the quality of madrasas at MTs Raden Rahmat Mojowarno is quite good with indicators a. Focus on customers both internal and external. Customer internal includes parents, students, teachers, administrators, staff and the board schools in the education system. While the customer External factors are the community, companies, families and universities. b. Total involvement of the institution by involving the entire community in the institution to participate in improving the quality of madrasas. c. Continuous improvement in the form of evaluating each component within the institution through monthly meetings organized by the madrasa, involving the community and stakeholders.